2022
DOI: 10.1002/jmv.28000
|View full text |Cite
|
Sign up to set email alerts
|

The deciphering of the immune cells and marker signature in COVID‐19 pathogenesis: An update

Abstract: The precise interaction between the immune system and severe acute respiratory syndrome coronavirus 2 (SARS‑CoV‑2) is critical in deciphering the pathogenesis of coronavirus disease 2019 (COVID‐19) and is also vital for developing novel therapeutic tools, including monoclonal antibodies, antivirals drugs, and vaccines. Viral infections need innate and adaptive immune reactions since the various immune components, such as neutrophils, macrophages, CD4 + T, CD8 + T, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 271 publications
2
9
0
Order By: Relevance
“…1 A). IFN-γ levels were similar over the different time-periods, both in SOT and no SOT, and without differences between groups (Supplementary Table 3), which is consistent with other studies 6 , 7 . RNAemia was more frequent in SOT recipients (57.4%) than in no SOT patients (18.9%, p<0.001) ( Fig.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…1 A). IFN-γ levels were similar over the different time-periods, both in SOT and no SOT, and without differences between groups (Supplementary Table 3), which is consistent with other studies 6 , 7 . RNAemia was more frequent in SOT recipients (57.4%) than in no SOT patients (18.9%, p<0.001) ( Fig.…”
supporting
confidence: 91%
“…Interferons (IFN) are key in the innate immune response during the acute phase of the viral infection, as seen with plasmacytoid dendritic cells expressing high concentrations of types I and III IFNs in COVID-19 patients 4 , 5 . In acute COVID-19 and convalescent patients, intracellular cytokine staining after stimulation with SARS-CoV-2 peptide pools, has showed significant IFN-γ increases in CD8 + T-cells, which is associated with viral elimination, and without differences in both phases of the disease 6 , 7 .…”
mentioning
confidence: 99%
“…Thus, the function of macrophage is most likely to be affected. Macrophages play an essential role in the COVID-19-associated cytokine storm ( Jasim et al, 2022 ). Our results showed that PSV caused a dramatically elevated expression of inflammatory markers (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It is also quite fascinating since the wide community of scientists suggests that Tregs during the SARS-CoV-2 infection get activated, suggesting their immunoregulatory or immunosuppressive activities to prevent immune cells of both innate and adaptive immune response from damaging self-tissues mainly by limiting the excessive release of pro-inflammatory cytokines and chemokines [ 20 , 82 ]. However, it is also possible that in the early stages of infection, a greater proportion of activated Tregs might weaken the immune system’s ability to fight off viruses such as SARS-CoV-2 [ 9 , 20 ].…”
Section: Possible Roles Of Tregs In Covid-19 Pathogenesis and Disease...mentioning
confidence: 99%